2001
DOI: 10.1080/108107301750254484
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Barriers to Preventive Health Actions for Occupational Noise-Induced Hearing Loss

Abstract: A theoretically based formative evaluation was conducted with coal miners in the Appalachian Mountains who were at high risk for noise-induced hearing loss (NIHL). The results of four focus groups indicate that despite high levels of knowledge, strong perceived severity of negative consequences, and strong perceived susceptibility to hearing loss, two main categories of barriers (environmental and individual) keep coal miners from using their hearing protection devices (HPD). Further analysis suggests that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 18 publications
(22 reference statements)
0
17
0
Order By: Relevance
“…[10] The use of hearing protection is further impacted by the inability of workers to communicate effectively when using them. [12,25] The workers felt that using HPDs cut them off from others and made them lonely. In addition, it was difficult and a hassle to remove hearing protection every time to communicate and then put them back on.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] The use of hearing protection is further impacted by the inability of workers to communicate effectively when using them. [12,25] The workers felt that using HPDs cut them off from others and made them lonely. In addition, it was difficult and a hassle to remove hearing protection every time to communicate and then put them back on.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Previous New Zealand research into of occupational exposure found that just half the plant and machine operators, assemblers, and elementary workers who worked in noisy environments reported hearing protection use. [9] Although international studies have looked at factors that influence the use of HPDs, [10][11][12][13] no such study has been found in New Zealand manufacturing workers. The purpose of this study was to understand the factors that influence the use of HPDs amongst a group of manufacturing workers in New Zealand.…”
Section: Introductionmentioning
confidence: 99%
“…According to the hierarchy of control, engineering and administrative controls are the first line of defence in the management of hazardous noise in the workplace, after elimination and substitution of the noise source (McBride, 2004;Patel et al, 2010;Rappaport and Provencal, 2001). However, evidence suggests that in practice, engineering and administrative controls are not given first priority (Suter, 2012).…”
Section: Management Of Onihlmentioning
confidence: 99%
“…ONIHL is the 'partial or complete hearing loss in one or both ears as a result of one's employment' (Nandi and Dhatrak, 2008, p. 1). This type of hearing loss develops gradually as a result of being exposed to continuous or intermittent high levels of noise over a long period of time (McBride, 2004;Patel et al, 2010;Rappaport and Provencal, 2001). A hearing threshold below 40 dBs is classified as a disabling hearing loss (Yadav et al, 2015), resulting in a hidden condition that does not readily manifest itself (Tye-Murray, 2009, p. 3).…”
Section: Introductionmentioning
confidence: 99%
“…While personal protective equipment (hearing protection) can control the hazard, some researchers indicate that there are strong workplace cultural factors that preclude their proper use Patel et al, 2001). It is therefore more effective to devise engineering controls for noise hazards.…”
Section: Introductionmentioning
confidence: 99%